The Experimental Research on Oscillation Character of The Static Gas Wave Refrigerator - Liu wei and Ji xiaohuiShenyang University of Technology China. (Zhileng xuebao)
The static gas wave refrigerator which depends on fluidic attachment and switching producing refrigeration was influenced by the movement of shock waved and expanding wave in oscillation tubes. So refrigeration efficiency depends on its oscillation character in large extent.The research on oscillation character can further improve the structure of refrigerator.This paper studied oscillation character when oscillating source was interconnection line and draw the following conclusions:1)To the static refrigerator with interconnection line,when length of tube line is very large the oscillation frequency is only relative to line length,otherwise it is influenced by inlet-pressure and line length.2)The interconnection line is used for lower oscillation frequency.3)The same fluidic can cause different intensity of shock wave in tubes.